Recent advances in silicon nanomaterials for lithium-ion batteries: Synthesis approaches, emerging trends, challenges, and opportunities - Hossain M.A.M.; Tiong S.K.; Hannan M.A.; Ker P.J.; Fattah I.M.R.; Mahlia T.M.I. (Elsevier B.V., 2025)
Lithium-ion batteries (LIBs) are essential for powering a wide range of current devices, including portable electronics and electric vehicles, because they have a high energy density, can be recharged, and are versatile. Silicon (Si)-based materials are being extensively studied as very promising anode compounds for future LIBs due to their moderate operating potential, high theoretical mass-specific capacity, and abundance. Consequently, it received considerable interest from both the academic and industrial sectors. However, electrochemical efficiency is hindered by significant changes in volume, leading to inadequate cyclability and eventual electrode malfunction. Nanostructured Si anodes address these issues by offering a reduced lithium diffusion distance, effective strain relaxation, improved mass transfer, and efficient electrical contact. The research on Si nanomaterials is highly significant due to the increasing need for improved energy density and safety in the rapidly developing field of energy storage. Recently, there have been attempts to mitigate the negative consequences of bulk effects, and nanosizing has emerged as a widely acknowledged and effective method. However, it has also encountered a limitation in its progress. Hence, this review aims to provide an in-depth overview of recent research on advances in Si materials, synthesis techniques, prevailing trends, and challenges, followed by emphasizing opportunities for future scientific study and commercial development of lithium-ion batteries. Overall, this review study holds significant merit as a reference tool for academics, researchers, and industry to explore research gaps and improve Si-based LIBs, which will shed light on solving the global energy crisis. ? 2024 Elsevier B.V.